High-resolution compositional remote sensing of the Transantarctic Mountains: application to the WorldView-2 dataset. Issue 5 (8th May 2015) - Salvatore, M.R.
Abstract: The WorldView-2 (WV2) instrument, operated by DigitalGlobe, is the only high-resolution multispectral sensor currently capable of imaging the entirety of the Transantarctic Mountains (TAM), making it a valuable resource for remote compositional investigations. Through the utility of both field- and laboratory-based verification techniques, this study shows that biotic and abiotic chemical variations can be readily observed and mapped remotely. Within the McMurdo Dry Valleys (MDV), primary compositional variability, intra-lithologic compositional heterogeneity and variations in surface weathering and oxidation can be successfully identified and mapped, providing confidence in both the spectral capabilities of the WV2 instrument and the methodologies associated with calibrating and correcting these data. These studies within the MDV provide confidence in extending these analyses to more remote regions of the TAM, including the vicinity of Shackleton Glacier. The identification of comparable geochemical variations in these remote locations provides valuable additions to the currently available geologic maps at much lower spatial resolutions. This work confirms the utility of the WV2 instrument to identifying, quantifying and mapping geochemical variations throughout the TAM, supporting future field work and providing geospatial context for localized field and laboratory analyses.